2022
DOI: 10.1002/sae2.12016
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of factors that influence farmers' adoption of sustainable crop farming practices: Lessons for sustainable nitrogen management in South Asia

Abstract: Despite the fact that sustainable agricultural technologies and practices have been developed and introduced to farmers in both developed and developing countries, there are concerns about low levels of adoption. Empirical evidence of the past 40 years shows that adoption of new practices can be hindered by a wide range of factors, from financial to attitudinal, from personal to social, from agronomic to regulatory.Conclusions that can be generalised across different contexts could help in moving the instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…The positive coefficient with the variable extension service argues that extension service recipient farmers have higher probability to adopt groundwater irrigation. This is coherent with literature arguing importance of extension service in technology dissemination, but to some extent contradicts with the literature highlighting importance of extension service for up-scaling sustainable agriculture practices (please see Begho et al, 2022 for a recent review on related literature). Since environmental sustainability in extension policy comes after food security through enhancing productivity, an extension agent may prioritize groundwater over surface water since the former ensures higher yield.…”
supporting
confidence: 49%
“…The positive coefficient with the variable extension service argues that extension service recipient farmers have higher probability to adopt groundwater irrigation. This is coherent with literature arguing importance of extension service in technology dissemination, but to some extent contradicts with the literature highlighting importance of extension service for up-scaling sustainable agriculture practices (please see Begho et al, 2022 for a recent review on related literature). Since environmental sustainability in extension policy comes after food security through enhancing productivity, an extension agent may prioritize groundwater over surface water since the former ensures higher yield.…”
supporting
confidence: 49%
“…Dairy ownership implies that farmyard manure is cheaply available (Pham et al., 2021), and it can also be an important income source for farm households in peri‐urban areas, where consumer demand for dairy products is high (Vandercasteelen et al., 2021). Farm size is typically considered an indicator for wealth; in addition, for sustainable practices that entail a large fixed‐cost component, it may be relevant when these can be spread over a bigger area of land (Begho et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The global food system is currently facing profound challenges related to ensuring the food security of a rising population and climate change, with extreme and unpredictable weather patterns, which jeopardize agricultural growth and the resilience of food production systems [5,6]. At the same time, agriculture is a major cause of environmental degradation, including greenhouse gas (GHG) emissions [5], soil erosion, water and air pollution, land degradation and biodiversity loss [7]. These environmental challenges negatively affect social and economic outcomes such as human welfare, social inclusion and economic prosperity, and they lead to the depopulation of rural areas [5,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Existing research has revealed a number of factors affecting farmer adoption of CSA practices, including technology, socioeconomic, psychological, farming structures, biophysical, institutional and policy factors [7,11,12]. To date, the existing literature has primarily employed the theories of reasoned action and planned behavior [13], the Theory of Diffusion of Innovations [14] and the Technology Acceptance Model [15] to investigate farmer decision-making processes.…”
Section: Introductionmentioning
confidence: 99%